Concepções de educação ambiental e perspectivas pedagógicas de professoras do ensino fundamental e as potencialidades do Pólo Ecológico de São Carlos (SP) - Iared, Valéria Ghisloti (Universidade Federal de São Carlos, 2010)
Since 1970´s, in Brazil, a series of educational proposals have incorporated activities related to environmental issues among then outdoor activities in natural spaces. However, we consider that most of those activities don´t take full advantage of its educational potential, both in order to explore all the contributions that the ecology field can offer, or to work with social mobilization and the formation of values. Moreover, it is relevant to identify how primary school teachers deal with three spheres of the educational practice (knowledge, ethical and aesthetics values, and participation) that we consider inseparable in an effective environmental education work. To investigate if the units of the São Carlos Ecological Pole (Pólo Ecológico de São Carlos) are educating spaces that contribute to the understanding of the complexity of environmental issues, and stimulate a sense of belonging and social responsibility, we interviewed primary school teachers who had accompanied visits to these places, people who are involved or have been involved with environmental education (EE) in these spaces, and followed guided tours in all units of the Ecological Pole. To present the results, we chose to discuss them in two stages: Moment I: analysis of all collected material trying to define what each unit of the Ecological Pole can offer, based on 21 listed parameters that are consistent with a critical perspective of EE and Moment II: an analysis of teachers´ interviews aiming to relate the different trends in environmental education conception and educational perspective. Regarding the Moment I, we have identified that the activities of EE in the Pole units can address issues that contemplate the three dimensions of educational practice. This brings up the idea that the issues involve more than one subject, which is consistent with our view that it is up to the EE to unveil the complexity of environmental issues. When we look at each site independent of each other, we realize that many parameters are not dealt with, but when considering the sum of these parameters, we observe that all are identified. This shows the importance of an EE that is permanent and continuous inter and transdisciplinary, requiring partnerships between multiple instances to be viable. The connectivity between the Pole units in a coordinated action would increase each unit´s actions. Therefore, we reinforce the idea that the integration of these units would yield a more thorough EE work. There are certain parameters that are still not addressed frequently. Thus, we envisage a permanent and articulated EE so that other issues, on occasions other than during these visits, can be discussed and reflected upon. For the Moment II analisys, we considered three perspectives of educational trends and three EE conceptual tendencies. We noticed the coexistence of several trends in the same speech, which indicates that the school is reflective and reflects the transition of paradigms through which society in general is going through, and hence the knowledge production in the EE field. From this evidence, we believe that the institutionalization of EE among different groups and social sectors can make the challenge of greening a less arduous task for the school. We identified that the EE actions, both at school and in field activities, do not incorporate all the points that deserve to be addressed in regard to the complexity of environmental issues. The results of this research show how an cross, permanent and continuous EE is a decisive factor for the realization of its principles and objectives.
Keywords: Educação ambiental; Espaços educadores; Áreas verdes urbanas; Dimensões da prática educativa; Educação escolar; Atividades ao ar livre; Educators spaces; Urban green areas; Educational practice dimensions; School environmental education; Outdoor activities; CIENCIAS BIOLOGICAS::ECOLOGIA